Bullying Dikalangan Pelajar dalam Perspektif Hukum Pidana Islam dan Hukum Positif di Indonesia (Studi Kasus di Kecamatan Medan Belawan) - Pradana, Ari; Yuslem, H. Nawir; Zulkarnain, Zulkarnain (Darul Yasin Al Sys, 2023)
Nowadays we often see various kinds of behavior among students, especially those who are in their teenage phase. And as one of their ways of expressing themselves, sometimes they will act a little aggressive and harsh, either through physical actions, or in the form of expressions that are usually called bullying. The problem taken in this research is related to how the views of Islamic Criminal Law and Positive Law in Indonesia regulate the crime of bullying which occurs among students, especially in Medan Belawan District. And the purpose of this research is to find out the factors that cause bullying crimes and what impacts will be caused by bullying crimes that occur in Medan Belawan District. The method used in this thesis research is a descriptive method in the form of qualitative research. Meanwhile, the approach used is empirical sociological. And the data sources in this research are students in Medan Belawan District and also the data obtained in this research are direct interviews with students in Medan Belawan District.